2020
DOI: 10.21675/2357-707x.2019.v10.n6.2253
|View full text |Cite
|
Sign up to set email alerts
|

Fiscalização do exercício profissional na área da saúde

Abstract: Objetivo: Identificar as características da fiscalização do exercício profissional realizadas por quatro conselhos profissionais da área da saúde. Metodologia: Estudo documental analítico, no qual foram incluídas leis de criação dos conselhos e resoluções vigentes que regulamentam a fiscalização do exercício profissional da Enfermagem, Medicina, Odontologia e Farmácia. Resultados: As profissões analisadas neste estudo possuem lei de criação de seus conselhos. A Enfermagem, a Medicina e a Farmácia possuem resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…E5 (14) Identificar as características da fiscalização do exercício profissional realizadas por quatro conselhos profissionais da área da saúde.…”
Section: Id* Objetivo Região Abordagem Principais Resultados Contribu...unclassified
See 2 more Smart Citations
“…E5 (14) Identificar as características da fiscalização do exercício profissional realizadas por quatro conselhos profissionais da área da saúde.…”
Section: Id* Objetivo Região Abordagem Principais Resultados Contribu...unclassified
“…Dentre os estudos selecionados, destacam-se pesquisas que envolveram o papel do enfermeiro fiscal, desafios e dificuldades no cotidiano do processo de trabalho, bem como os custos relativos à mão de obra direta dos fiscais (11)(12)18) . Outras pesquisas destacaram a importância e as características do setor de fiscalização dos do COFEN e COREN no Brasil e sua contribuição para melhoria da qualidade da assistência (10,(13)(14)(15)(16)(17) .…”
Section: Análise Dos Dadosunclassified
See 1 more Smart Citation
“…In relation to professional advice in the health sector, research observed that, when analyzing the professions of nursing, dentistry, medicine and pharmacy, nursing is the only one that has an audit process based on Resolutions with an educational character, encouraging ethical values and valuing the work process ( 14 ) . However, the need to consolidate these precepts and strengthen these activities is discussed, in order to expand legislation into practice ( 10 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, nursing inspection process challenges are anchored in the difficulties related to the nurses' lack of ethical-legal knowledge, deficient nursing dimensioning, and lack of a standardization in the inspection process (16)(17) . Similarly, in the international context, divergences in regulatory laws suggest the political weakening As for the outcomes of the 182 ethical lawsuits filed, 76 (41.8%) were acquitted by the Plenary of the Council, 56 (30.8%) had penalties applied.…”
Section: Discussionmentioning
confidence: 99%